Analisis Pemikiran Haidar Bagir Dalam Perspektif Hukum Keluarga Islam: Makna Sakinah Pernikahan - Apriansyah; Farah Batrisyia Binti Mohd Ridzwan; Pramudya Wisesha (Institut Agama Islam Negeri Metro, 2025)
The concept of sakinah in Islamic family law is often narrowly understood as peace and tranquility in the household. However, Haidar Bagir offers a more comprehensive interpretation of sakinah, emphasizing justice, equality, and respect for individual rights within the family. Therefore, this study aims to analyze Bagir’s thoughts on sakinah within the framework of contemporary Islamic family law, using a hermeneutic and contextual approach. This method prioritizes dialogue between classical texts and socio-historical contexts to find legal solutions that are relevant to modern dynamics. Furthermore, the research shows that Bagir’s ideas address gender inequality, advocate for equal rights and responsibilities between spouses, and promote respect for women and children's rights. In addition, his hermeneutic approach allows for a more responsive interpretation of Islamic law to accommodate social and cultural developments. As a result, Bagir's thought significantly contributes to deconstructing conservative paradigms in Islamic family law and introduces a more inclusive and just concept of family.